(x+1/x2+5x-14)x=0

Simple and best practice solution for (x+1/x2+5x-14)x=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+1/x2+5x-14)x=0 equation:



(x+1/x2+5x-14)x=0
Domain of the equation: x2+5x-14)x!=0
x∈R
We add all the numbers together, and all the variables
(6x+1/x2-14)x=0
We multiply parentheses
6x^2+x^2-14x=0
We add all the numbers together, and all the variables
7x^2-14x=0
a = 7; b = -14; c = 0;
Δ = b2-4ac
Δ = -142-4·7·0
Δ = 196
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{196}=14$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-14)-14}{2*7}=\frac{0}{14} =0 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-14)+14}{2*7}=\frac{28}{14} =2 $

See similar equations:

| 9(k+9)-(8k+3)=-2 | | -9(t—2)=4(t—15) | | |3y+1|=10 | | 7x+3-2×+7=180 | | -9(t–2)=4(t–15) | | 11a-11=15+9a | | -3r+10=15r–8 | | X/8+x/2=-2 | | 55-23y=14 | | -3r+10=15r—8 | | 4/3x+2/3x=1/3+5 | | 0.5x+0.25=0.33x+1.25 | | x3-11=29 | | 3(x+9)^2-12=63 | | 4u+16=68 | | -4=5x=2(3x-4) | | 21=x/3+12 | | 7x-12=8x=29-x | | −x+4(1+5x)=156 | | 25-x=15-(x+10) | | 3b=b-18 | | 3a+2=×-6 | | 0=x^​2/3+2x+2.8 | | (2x^-3)-1=15 | | 2x^-3-1=15 | | 2(x-3)+4=5-(x+1) | | 59.95+7.33x=6.14 | | 4x-3x^2+8=0 | | 9x^2+6x=12 | | 8×b=27 | | ​1/2r−3=3(4−​2/​3r) | | 3x+2+5x-4x=0 |

Equations solver categories